PULMONARY VASODILATORS EFFECT IN BIDIRECTIONAL GLENN ANASTOMOSIS FOR HIGHER GLENN PRESSURES - Ahmed Ibrahim Ismail; Martin Kostelka; Ingo Dähnert; Ahmed Ghoneim; Ahmed Nabil Malek; Ahmed Mohamed Abdelhakim Mekkawy (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
: Bidirectional Glenn operations are commonly performed on patients with a single ventricle as part of the staged surgical management process. Inhaled nitric oxide is a famous pulmonary vasodilator that can be used to treat elevated Glenn pressure following surgery, but still is not offered in many cardiac centers of developing countries. The purpose of this study was to compare the results of inhaled nitric oxide therapy in comparison with a combination of milrinone and sildenafil for management of significant rise in Glenn pressures after this procedure.Methods: An eighteen-year retrospective study was conducted. After starting pulmonary vasodilator therapy, the change in Glenn pressures was assessed in both groups and compared with baseline parameters. The impact of inhaled nitric oxide therapy was compared with milrinone and sildenafil combination in postoperative marked elevations of Glenn pressures.Results: Twelve patients were treated with nitric oxide (NO) therapy in group (A) for high rises of Glenn pressure (23.4± 2.3 mm Hg). There were significant decrease in Glenn pressure in 10 patients (from 23.2 mm Hg to 18.2 mm Hg, p < 0.00001) and significant rise in partial pressure of oxygen to fraction of inspired oxygen ratio (from 49.7 to 72.4, p < 0.01). There were insignificant reductions in inotrope score (from 14.5 to 11.2, p < 0.3) in the responsive patients. There were two patients who did not respond at all. Thirteen patients were placed on milrinone and sildenafil Combination therapy in group (B) for marked rises in Glenn pressures (25.1± 3.1 mm Hg). In the eleven patients, there were decreases in Glenn pressures (from 25.1 mmHg to 17.9 mm Hg, p < 0.00001) and significant rise in partial pressure of oxygen to fraction of inspired oxygen ratio (from 50.2 to 74.3, p < 0.01). There was coincident insignificant decrease in inotrope score (from 15.1to 13.9, p < 0.68) in the responsive patients. There were three patients who did not respond. Conclusion: Patients who have markedly elevated Glenn pressures following bidirectional Glenn anastomosis benefit from inhaled nitric oxide versus combination therapy of milrinone and sildenafil, which both significantly lower Glenn pressures and improve systemic blood pressure and pulmonary function. Failure of management is attributed mostly for surgical problems.